2016
DOI: 10.1186/s12872-016-0212-8
|View full text |Cite
|
Sign up to set email alerts
|

Non alcoholic fatty liver disease increases the mortality from acute coronary syndrome: an observational study from Sri Lanka

Abstract: BackgroundNon alcoholic fatty liver disease is an independent risk factor for coronary artery disease. But its effect on acute coronary syndrome is not clear. We performed this study to identify the prevalence of NAFLD in patients with ACS admitted to a tertiary care center in Sri Lanka. We also described the association of NAFLD with the severity of ACS predicted by the GRACE score.MethodsWe performed a descriptive study including all consecutive patients with non-fatal ACS admitted to Colombo South Teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
4
29
1
2
Order By: Relevance
“…In their study, NAFLD was present in 45.7% of the 542 patients [10]. is study shows that age and NAFLD are important factors contributing to cardiovascular disease-related deaths [10]. In the study by Agaç et al, the prevalence of NAFLD was 81.2% [6].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In their study, NAFLD was present in 45.7% of the 542 patients [10]. is study shows that age and NAFLD are important factors contributing to cardiovascular disease-related deaths [10]. In the study by Agaç et al, the prevalence of NAFLD was 81.2% [6].…”
Section: Discussionmentioning
confidence: 93%
“…Ling and Shu-zheng showed that patients with NAFLD had a high severity of CAD [16]. In their study, NAFLD was present in 45.7% of the 542 patients [10]. is study shows that age and NAFLD are important factors contributing to cardiovascular disease-related deaths [10].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Increased age and presence of NAFLD conferred a higher mortality risk from ACS as predicted by GRACE score [52].…”
Section: Depiction Of the Magnitude Among Different Risk Groupmentioning
confidence: 99%